Climate Change Impact on the Magnitude and Timing of Hydrological Extremes Across Great Britain - Lane, Rosanna A.; Kay, Alison L. (Frontiers in Water, 2021)
Climate change could intensify hydrological extremes, changing not just the magnitude but also the timing of flood and drought events. Understanding these potential future changes to hydrological extremes at the national level is critical to guide policy decisions and ensure adequate adaptation measures are put in place. Here, climate change impact on the magnitude and timing of extreme flows is modelled across Great Britain, using an ensemble of climate data from the latest UK Climate Projections product (UKCP18) and a national grid-based hydrological model. All ensemble members show large reductions in low flows, of around -90 to -25% for 10-year return period low flows by 2050-2080. The direction of change for high flows is uncertain, but increases in 10-year return period high flows of over 9% are possible across most of the country. Simultaneous worsening of both extremes (i.e. a reduction in low flows combined with an increase in high flows) are projected in the west. Changes to flow timing are also projected; with mostly earlier annual maximum flows across Scotland, later annual maximum flows across England and Wales, and later low flows across GB. However, these changes are generally not statistically significant due to the high interannual variability of annual maximum/minimum flow timing. These results highlight the need for adaptation strategies that can cope with a wide range of future changes in hydrological extremes, and consider changes in the timing as well as magnitude.